Limites de desafios na configuração dos órgãos gestores da Política Municipal de Assistência Social da Região Noroeste Paulista: municípios de pequeno porte - Ferreira, Cecília Ketelhute Franco de Carvalho (2014)
This study examines the management of Social Welfare Policy at the regional and municipal levels, and has as base the normative axis of Social Welfare Policy. To understand this dynamic, it was considered a regional training, analyzing the historical, political and economic contexts of the region. One sees common characteristics among municipalities, as well as the particularities of each of the possible paths to discuss the factors that influence the institutionalization of social assistance as a public policy rights. The spatial dimension of this work is limited to the municipalities that make up the administrative region of the Regional Directorate of Social Development (Drads) Araçatuba, comprising forty-three municipalities in the State of São Paulo. The work brings together elements for analysis of the process of managing the social assistance policy, based on nationally agreed normative, and then it analyzes how is the manifestation of the sphere circumscribed municipalities in the region delimited in this study. Reports the historical, economic and political history of the municipalities, and then builds an inventory of available data on the Internet, specifically the websites of the forty-three municipalities of the region. Decoding these connections allows to know and assert whether municipalities have used virtual resources to present Social Assistance Policy as required by PNAS. Later contextualizes the politics of Social Welfare in the State of São Paulo, under the action of the Regional Social Development Division (Drads), and how it gives the dynamics in this sphere and its relationship with municipalities. In the last chapter first is presented the fieldwork carried out in a group of municipalities in the region of Araçatuba, and by the results of this first access to information, the study is delimited to the analysis of social assistance, after the implementation of the Suas (Single Social Assistance System), a group of small municipalities "1", considered 81% of all municipalities in this region. The final considerations present reflections on the difficulties and advances seen in the efforts of the Social Assistance Policy, the regional and municipal level, in order to contribute to building a more totalizing approaches the Single Social Assistance System